Cultural Integration and Globalization of Criminal Justice - (:unkn) unknown (My University, 2016)
This contribution focuses on one aspect of social justice, namely criminal justice. It studies the growing development of criminal justice at the international level, and wishes to understand to which extent globalization has been achieved, and in what general context this globalization can operate. In this sense, this contribution has a double objective: on the one hand, it is aimed at deepening our theoreticalunderstanding of the globalization of criminal justice, and its context of human rights cultures; on the other hand, it wishes to provide some keys for a more comprehensive functioning of criminal justice at the global level.